Mechanical response of human subclavian and iliac arteries to extension, inflation and torsion. (15th July 2018) - Sommer, Gerhard; Benedikt, Christoph; Niestrawska, Justyna A.; Hohenberger, Gloria; Viertler, Christian; Regitnig, Peter; Cohnert, Tina U.; Holzapfel, Gerhard A.
Graphical abstract: Abstract: Peripheral vascular trauma due to injuries of the upper and lower limbs are life-threatening, and their treatment require rapid diagnosis and highly-qualified surgical procedures. Experienced surgeons have recognized that subclavian arteries, affected by injuries of the upper limbs, require a more careful handling due to fragility than common iliac arteries, which are may be affected by injures of the lower limbs. We investigated these two artery types with comparable diameter to evaluate the differences in the biomechanical properties between subclavian and iliac arteries. Human subclavian and common iliac arteries of 14 donors either from the right or the left side (age: 63 yrs, SD: 19, 9 female and 5 male) were investigated. Extension-inflation-torsion experiments at different axial strains (0–20%), transmural pressures (0–200 mmHg) and torsion ( ± 25 ° ) on preconditioned arterial tubes were performed. Residual stresses in both circumferential and axial direction were determined. Additionally, the microstructure of the tissues was determined via second-harmonic generation imaging and by histological investigations. At physiological conditions ( p i = 13.3 kPa, λ z = 1.1 ) common iliac arteries revealed higher Cauchy stresses in circumferential and axial directions but a more compliant response in the circumferential direction than subclavian arteries. Both arteries showed distinct stiffer behavior in circumferential than in axial direction. Circumferential stiffness of common iliac arteries at physiological conditions increased significantly with aging ( r = - 0 . 67, p = 0 . 02 ). The median inversion stretches, where the axial force is basically independent of the transmural pressure, were determined to be 1.05 for subclavian arteries and 1.11 for common iliac arteries. Both arteries exhibited increased torsional stiffness, when either axial prestretch or inflation pressure was increased. Residual stresses in the circumferential direction were significantly lower for subclavian arteries than for common iliac arteries at measurements after 30 min ( p = 0.05 ) and 16 hrs ( p = 0.01 ). Investigations of the collagen microstructure revealed different collagen fiber orientations and dispersions in subclavian and iliac arteries. The difference in the collagen microstructure revealed further that the adventitia seems to contribute significantly to the passive mechanical response of the tested arteries at physiological loadings. Histological investigations indicated pronounced thickened intimal layers in subclavian and common iliac arteries, with a thickness comparable to the adventitial layer. In conclusion, we obtained biomechanical differences between subclavian and common iliac arteries, which possibly resulted from their different mechanical loadings/environments and respective in vivo movements caused by their anatomical locations. The biomechanical differences explored in this study are well reflected by the microstructure of the collagen and the histology of the investigated arteries, and the results can improve trauma patient care and endovascular implant design. Statement of Significance: During surgical interventions surgeons experienced that subclavian arteries (SAs) supplying the upper extremities, appear more fragile and prone to damage during surgical repair than common iliac arteries (CIAs), supplying the lower extremities. To investigate this difference in a systematic way the aim of this study was to compare the biomechanical properties of these two arteries from the same donors in terms of geometry, extension-inflation-torsion behavior, residual stresses, microstructure, and histology. In regard to cardiovascular medicine the material behavior of aged human arteries is of crucial interest. Moreover, the investigation of SA is important as it can help to improve surgical procedures at this challenging location. Over the long-term it might well be of value in the construction of artificial arteries for substituting native arteries. In addition, the analysis of mechanical stresses can improve design and material choice for endovascular implants to optimize long-term implant function.